2015
DOI: 10.1016/j.jaut.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Renal involvement in lupus is characterized by unique DNA methylation changes in naïve CD4+ T cells

Abstract: Systemic lupus erythematosus is a multi-system disease characterized by wide-spread DNA methylation changes. To identify epigenetic susceptibility loci for lupus nephritis, genome-wide DNA methylation changes in naïve CD4+ T cells were compared between two sets of lupus patients with and without a history of renal involvement. A total of 56 lupus patients (28 with renal involvement and 28 without renal involvement), and 56 age-, sex-, and ethnicity-matched healthy controls were included in our study. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 25 publications
2
82
3
1
Order By: Relevance
“…, and CD40L [21][22][23][24]. The events that initiate these disease-related epigenetic alterations are not clear, but in some cases appear to involve a reduction in DNA methyltransferase activity [24].…”
Section: Cd70mentioning
confidence: 99%
“…, and CD40L [21][22][23][24]. The events that initiate these disease-related epigenetic alterations are not clear, but in some cases appear to involve a reduction in DNA methyltransferase activity [24].…”
Section: Cd70mentioning
confidence: 99%
“…Epigenetic mechanisms are believed to integrate environmental influences on gene expression, possibly affecting immune system dysregulation and autoimmune manifestations (3). In this regard, epigenetic variation has been associated with various rheumatic diseases, including adult rheumatoid arthritis (RA) (4,5), lupus (6,7), and JIA (8). In addition, Liu et al (9) identified two differentially methylated regions within the major histocompatibility complex (MHC) locus between RA patients and healthy controls, and suggested that a proportion of the risk conferred by the MHC region in RA is in fact mediated by altered DNA methylation.…”
mentioning
confidence: 99%
“…[77, 78] The association between wide-ranged DNA hypomethylation in lupus and disease activity is on the basis of the study that applying DNA methylation inhibitors in CD4+ T cells would lead to a lupus-like syndrome. Recent studies applying sequence analysis technology have gained meaningful results that provide us with more information about lupus heritability [79], ethnicity variance [80] and renal involvement with DNA methylome analysis in CD4+ T cells [81]. Coit et al confirmed a group of interferon-related genes that are aberrantly hypomethylated, including IFN-induced protein 44-like (IFI44L), IFN-induced protein with tetratricopeptide (IFIT1), IFIT3, MX dynamin-like GTPase 1 (MX1), signal transducer and activator of transcription 1 (STAT-1), bone marrow stromal cell antigen 2 (BST2) and tripartite motif containing 22 (TRIM22), in lupus CD4+ T cells [82].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%